2020
DOI: 10.3390/ani10122376
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Distribution of Neoplasia among Non-Domestic Felid Species under Managed Care

Abstract: As evidenced by numerous case reports from zoos, neoplasia in felids is common, but most reports are limited to Panthera species in North America or Europe. In order to obtain a wider epidemiologic understanding of neoplasia distribution, necropsy records at seven facilities (USA, Mexico, Colombia, Peru, and Brazil) were evaluated. In contrast to others, this study population (195 cases, 16 species), included many non-Panthera felids. Overall neoplasia prevalence was 28.2% (55/195). Panthera species had a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…High cancer risk in managed populations of Carnivora has previously been reported 23,24 . Possible explanations include the use of hormonal contraception (for example, progestins) and pregnancy postponement in zoo carnivores, both being significant risk factors for certain cancers in humans as well as non-domestic felids [24][25][26] .…”
Section: Cancer Across the Mammalian Phylogenymentioning
confidence: 92%
See 1 more Smart Citation
“…High cancer risk in managed populations of Carnivora has previously been reported 23,24 . Possible explanations include the use of hormonal contraception (for example, progestins) and pregnancy postponement in zoo carnivores, both being significant risk factors for certain cancers in humans as well as non-domestic felids [24][25][26] .…”
Section: Cancer Across the Mammalian Phylogenymentioning
confidence: 92%
“…Pairwise comparison between sexes revealed no sex bias in either measure of cancer mortality risk (phylogenetic paired t -tests, CMR: t = 0.52, df = 33, P = 0.6061; ICM: t = −0.6815, df = 27, P = 0.5014) (ref. 23 ). Therefore, the generally high cancer risk in Carnivora is unlikely to be driven solely by the carcinogenic effects of reproductive management in zoo populations.…”
Section: Cancer Across the Mammalian Phylogenymentioning
confidence: 99%
“…It has been suggested that there may be a genetic predisposition/propensity for the development of neoplasia at the Panthera genus (or higher) level, which may be compounded by mutations from in‐breeding in captive populations (Moresco et al., 2020). In a study of 195 cases of neoplasia in 16 species of non‐domesticated felid species living under managed care (80 and 115 cases of Pathera and non‐ Panthera species, respectively), the Panthera species had a significantly higher prevalence of neoplasia than non‐ Panthera species (50% vs. 13%, respectively), with the percentage of malignant neoplasms also significantly higher in the Panthera species (86% vs. 61% respectively) (Moresco et al., 2020). The reproductive system (reproductive organs and mammary glands) was the most commonly affected system (21% of cases), followed by the haematolymphoid system (18%) and the respiratory system (16%) (Moresco et al., 2020), with only one case involving the urinary system (UC of the urinary bladder in a lion).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 195 cases of neoplasia in 16 species of non‐domesticated felid species living under managed care (80 and 115 cases of Pathera and non‐ Panthera species, respectively), the Panthera species had a significantly higher prevalence of neoplasia than non‐ Panthera species (50% vs. 13%, respectively), with the percentage of malignant neoplasms also significantly higher in the Panthera species (86% vs. 61% respectively) (Moresco et al., 2020). The reproductive system (reproductive organs and mammary glands) was the most commonly affected system (21% of cases), followed by the haematolymphoid system (18%) and the respiratory system (16%) (Moresco et al., 2020), with only one case involving the urinary system (UC of the urinary bladder in a lion). Prior to the case presented here, it was the only reported case of UC in a member of the Panthera species, consistent with the rarity of reports of UC of the urinary bladder in non‐domestic felids, having been reported in fishing cats (Sutherland‐Smith et al., 2004), and a Pallas’ cat (Moresco et al., 2020), and the relatively low incidence of UC in domestic cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation